2018
DOI: 10.1177/0266242618796145
|View full text |Cite
|
Sign up to set email alerts
|

Effectuation, network-building and internationalisation speed

Abstract: We extend research on the speed of new venture internationalisation by distinguishing between effectual and non-effectual (i.e. causal) network-building approaches, and conceptualising their differential effects on the dimensions of initial entry speed, country (i.e. international) scope speed and international commitment speed. Drawing upon the extant literature on internationalisation speed, network building and effectuation theory, we argue that an effectual approach to networkbuilding is positively associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(136 citation statements)
references
References 88 publications
(186 reference statements)
8
124
1
3
Order By: Relevance
“…Starting from an attempt to complement our view of IE with a sense-making perspective (Weick 1995;Rasmussen et al 2001)-hence to include alternative interpretations of individual entrepreneurial behavior-we sought to apply our methods in such a way as to encompass the Bfragile, emerging and provisional character of any kind of 'unit' that emerges from and is embedded within a process ( Steyaert 2007: 459). We also applied principles of narrative inquiry into human life experiences (Polkinghorne 1988;Riessman 1993), which see as having made major contributions to the study of human cognition, by drawing upon script theory and autobiographic memory (Hiles and Cermák 2008). Accordingly, we made use of life narratives as Bscripts^ (McAdams 2006).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Starting from an attempt to complement our view of IE with a sense-making perspective (Weick 1995;Rasmussen et al 2001)-hence to include alternative interpretations of individual entrepreneurial behavior-we sought to apply our methods in such a way as to encompass the Bfragile, emerging and provisional character of any kind of 'unit' that emerges from and is embedded within a process ( Steyaert 2007: 459). We also applied principles of narrative inquiry into human life experiences (Polkinghorne 1988;Riessman 1993), which see as having made major contributions to the study of human cognition, by drawing upon script theory and autobiographic memory (Hiles and Cermák 2008). Accordingly, we made use of life narratives as Bscripts^ (McAdams 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, the interviews themselves exist as opportunities for B(re)constructing narratives in different ways, evolving different perspectives on the past, leading to different understandings of the present, with implications for the future^ (Birch and Miller 2000: 93; referring also to Ricoeur 1991;Rosenthal 1993). Overall, there is a well-theorized and thoroughly analyzed link between the construction of identity (Bruner 1995;Riessman 1993) and the mental representations of individuals structured in terms of narratives (Polkinghorne 1988). Of particular relevance for this study is the recognition of narrative as fundamental in the formation of entrepreneurial identity (Jones et al 2008;Mills and Pawson 2006;Nielsen and Lassen 2012;Yitshaki and Kropp 2016).…”
Section: Datamentioning
confidence: 98%
See 2 more Smart Citations
“…It has been suggested that entrepreneurs are able to shift between the use of effectuation and causation (Schreier and Senn 2018;Andersson 2011). The effectual approach to network-building has been explained to be positively associated with initial entry speed and international scope speed while a causal approach is negatively associated with initial entry speed and international scope speed (Prashantham et al 2019). Galkina and Chetty (2015) also show that entrepreneurs of small and medium enterprises network with interested partners, instead of carefully selecting international partners according to predefined network goals.…”
mentioning
confidence: 99%